Elevator Control Using Speech Recognition for People with Physical Disabilities - ., Andriana; Vertus, Olly; Setiyono, Riyanto; ., Zulkarnain; ., Pamungkas (International Journal of Engineering and Technology, 2019)
This research will make the design of elevators that can be helpful for persons with disabilities, namely elevators controlled by voice. Disability is someone who does not have a complete hand organ or hand organs but does not function properly, but the person can still use voice to control the elevator. The research combines speech recognition technology with electronic control technology used to make the elevator control equipment that can be controlled by voice. Speech Recognition is a system that functions to convert spoken language into the input data. The system input is human speech. The system will identify spoken words to input data for control equipment. Control of this equipment requires a simple word and can only recognize some words. These systems are usually more accurate and more easily trained, but could not recognize words that are beyond vocabulary ever taught. This system uses a sensor device sound which call Easy Voice Recognition for the training process and the minimum word recognition and for control system using arduino Uno. The word can be trained for a maximum of 32 words. The test results stated all words can be recognized as a command to control the elevator.Â Â